Strategic Planning Using SWOT Matrix and QSPM: Case Study Analysis at Prima Fotocopy Center - Devina Putri; Tri Siwi Agustina; R. Aj. Diajeng Widiani H.; Nikita Claudia (CV. AFDIFAL MAJU BERKAH, 2026)
Prima Fotocopy Center is a photocopying center business that provides black and white and color photocopying services. Prima Photocopy Center was established on January 20, 1998, in Bima City, West Nusa Tenggara. The study was conducted for 3 weeks, namely on December 18–January 7, 2024 in Bima City, West Nusa Tenggara. The purpose of this study is to determine the strategic planning for the development of